Reviews of Flight Attendants towards the Tourism Program: Case of the Lyceum of the Philippines University - Krisca Mae A. Paguinto; Ziryl F. Rosarito; Ma. Theresa L. Lamanilao; Allyssa Marey R. Salvador; Rovena Dellova (International Journal of Applied Research in Tourism and Hospitality, 2022)
This study looked into the recommendations and views of Filipino flight attendants on the level of importance of the courses, their training experiences, and recommendations that serve as a window to consider the improvement of the tourism program. This descriptive study utilized a post-hoc analysis of version 2.0 with 72 respondents currently or formerly employed as flight attendants. They constitute 50% of the population proportion of 140 identified Filipino flight attendants from different airlines, both international and local, having 11.50% precision at a .05 significance level. A purposive type of sampling method mixed with the snowball technique was utilized in this study. In-Flight Attendant program offering, the study reveals that minor courses were rated as “highly important” specifically in Communication subjects while major courses were rated “very highly important”. Among the 29 listed major courses, Risk Management as Applied to Safety, Security, and Sanitation ranked first, followed by Global Culture and Tourism Geography, followed by Professional Development and Applied Ethics. Moreover, most of the respondents faced challenges over inadequate knowledge of aircraft equipment and emergency procedures. It is highly recommended by some of the current Filipino flight attendants to enhance and/or add courses/activities related to Basic Life Support, Personality Development, Communication Skills Development, Customer Service, and Aircraft-related courses.